(untitled) - Marton, Peter (Doprava a spoje, 2009)
Freight railway transport in CEEC has changed significantly in last 20 years. After political changes in 1989, economic system was shifted. In 2004 and 2007 former socialist countries entered in European Union. The aim of this paper is to analyze development of freight railway transport in CEEC, discuss the reasons of this development and describe current status of freight railway market.